An analysis of the performance of deconstructed tires for use as pads in railroad tracks - Sol-Sánchez, Miguel; Moreno-Navarro, Fernando; Rubio-Gámez, Maria Carmen (Journal of Civil Engineering and Management, 2016)
The use of end-of-life (EOL) tires is now widespread in civil engineering work. In most cases, the tires are shredded and recycled as crumb rubber. However, this research focuses on an alternate method in which EOL tires were deconstructed to manufacture rail pads. In other words, their outer layer was removed, which made it possible to benefit from the mechanical properties of the tires without having to grind them up. The performance of the recycled tire rubber was analyzed by means of static and dynamic stiffness tests as well as by fatigue tests. The results reflected the long-term performance of the material. Also analyzed was the deterioration of its properties after various thermal and anti-ageing treatments. The results obtained were compared with those of commercial crumb rubber rail pads. The excellent performance of the rail pads made from deconstructed EOL tires shows the high potential of this material for use in railroad tracks.